A promiscuous coenzyme A ligase provides benzoyl‐coenzyme A for xanthone biosynthesis in Hypericum. (3rd November 2020) - Singh, Poonam; Preu, Lutz; Beuerle, Till; Kaufholdt, David; Hänsch, Robert; Beerhues, Ludger; Gaid, Mariam
SUMMARY: Benzoic acid‐derived compounds, such as polyprenylated benzophenones and xanthones, attract the interest of scientists due to challenging chemical structures and diverse biological activities. The genus Hypericum is of high medicinal value, as exemplified by H. perforatum . It is rich in benzophenone and xanthone derivatives, the biosynthesis of which requires the catalytic activity of benzoate‐coenzyme A (benzoate‐CoA) ligase (BZL), which activates benzoic acid to benzoyl‐CoA. Despite remarkable research so far done on benzoic acid biosynthesis in planta, all previous structural studies of BZL genes and proteins are exclusively related to benzoate‐degrading microorganisms. Here, a transcript for a plant acyl‐activating enzyme (AAE) was cloned from xanthone‐producing Hypericum calycinum cell cultures using transcriptomic resources. An increase in the Hc AAE1 transcript level preceded xanthone accumulation after elicitor treatment, as previously observed with other pathway‐related genes. Subcellular localization of reporter fusions revealed the dual localization of Hc AAE1 to cytosol and peroxisomes owing to a type 2 peroxisomal targeting signal. This result suggests the generation of benzoyl‐CoA in Hypericum by the CoA‐dependent non‐β‐oxidative route. A luciferase‐based substrate specificity assay and the kinetic characterization indicated that Hc AAE1 exhibits promiscuous substrate preference, with benzoic acid being the sole aromatic substrate accepted. Unlike 4‐coumarate‐CoA ligase and cinnamate‐CoA ligase enzymes, Hc AAE1 did not accept 4‐coumaric and cinnamic acids, respectively. The substrate preference was corroborated by in silico modeling, which indicated valid docking of both benzoic acid and its adenosine monophosphate intermediate in the Hc AAE1/BZL active site cavity. Significance Statement: The central intermediate of benzenoid biosynthesis within phenylpropanoid metabolism is benzoyl‐coenzyme A, which arises by multiple pathways and represents the precursor for numerous downstream routes leading to a variety of natural products. Here, we report cDNA cloning, functional characterization, subcellular localization and homology modeling of an acyl‐activating enzyme, which catalyzes formation of benzoyl‐coenzyme A.